2015
DOI: 10.1038/ng.3218
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo effector YAP promotes resistance to RAF- and MEK-targeted cancer therapies

Abstract: Resistance to RAF- and MEK-targeted therapy is a major clinical challenge1–4. RAF and MEK inhibitors are initially but only transiently effective in some but not all patients with BRAF gene mutation and are largely ineffective in those with RAS gene mutation because of resistance5–14. Through a genetic screen in BRAF-mutant tumor cells, we show that the Hippo pathway effector YAP (encoded by YAP1) acts as a parallel survival input to promote resistance to RAF and MEK inhibitor therapy. Combined YAP and RAF or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
393
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 460 publications
(450 citation statements)
references
References 36 publications
22
393
1
Order By: Relevance
“…In some tumours, BRAF and MEK inhibition has been observed to increase signalling through the YAP pathway 127 , leading to escape from cell death via increased expression of the antiapoptotic protein Bcl-xL 128 (FIG. 4a).…”
Section: Braf-mek-inhibitor Resistance and Biomarkersmentioning
confidence: 99%
“…In some tumours, BRAF and MEK inhibition has been observed to increase signalling through the YAP pathway 127 , leading to escape from cell death via increased expression of the antiapoptotic protein Bcl-xL 128 (FIG. 4a).…”
Section: Braf-mek-inhibitor Resistance and Biomarkersmentioning
confidence: 99%
“…4,5 Resistance to RAF-MEK targeted therapy is a major clinical challenge. RAF-MEK inhibitors are initially, but only transiently, effective in some, but not all, patients with BRAF-mutant disease, and largely ineffective in patients with RASmutant disease because of resistance.…”
mentioning
confidence: 99%
“…6 We used a pooled small hairpin RNA screen in human BRAF V600E mutant lung cancer cells to identify genes that when silenced enhanced the response to the approved BRAF inhibitor vemurafenib. 4 Through this genetic screen, we found that the Hippo pathway effector yes-associated protein 1 (YAP1) acts as a parallel survival input to promote resistance to RAF-MEK inhibitor therapy ( Fig. 1).…”
mentioning
confidence: 99%
“…Secondly, activation of YAP1, already described by Dr. Rosell's group as a factor involved in resistance to targeted drugs (10,11), leads to the acquisition of an immunoresistant phenotype by promoting the expression of immunosuppressive molecules EOMES and PD-1 (12), as well as the secretion of the chemokine CXCL5, leading to increased tumor infiltration by immunosuppressive cells, called myeloid derived suppressor cells (MDSCs) (13).…”
Section: Inspiring Talksmentioning
confidence: 99%